Template Subtraction to Remove CI Stimulation Artifacts in Auditory Steady-State Responses in CI Subjects - Deprez, Hanne; Gransier, Robin; Hofmann, Michael; van Wieringen, Astrid; Wouters, Jan; Moonen, Marc (IEEE transactions on neural systems and rehabilitation engineering, 2017)
Cochlear implant (CI) stimulation artifacts are currently removed from electrically evoked steady-state response (EASSR) measurements based on a linear interpolation (LI) over the artifact-contaminated signal parts. LI is only successful if CI stimulation artifacts are shorter than the interpulse interval, i.e., for contralateral channels and stimulation pulse rates up to 500 pulses per second (pps). The objective of this paper is to develop and evaluate a template subtraction (TS) method to remove continuous CI stimulation artifacts in order to accurately measure EASSRs. The template construction (TC) is based on an EEG recording containing CI stimulation artifacts but no synchronous neural response. The constructed templates are subtracted from the recording of interest. Response amplitudes and latencies are compared for the TS and LI method, and for different TC durations. The response amplitudes and latencies in contralateral channels are the same after TS and LI, as expected. In ipsilateral channels, response amplitudes and latencies are within the expected range only after TS. The TC duration can be reduced from 5 min to 1 min without a significant effect on response latency. TS with a TC duration of only 1 min allows to remove all CI stimulation artifacts in individual contra- and ipsilateral EEG recording channels.